2007
DOI: 10.1159/000100086
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Intermittent Hypoxemia to Late Neurological Handicap in Mice with Hyperoxia-Induced Lung Injury

Abstract: Bronchopulmonary dysplasia (BPD) is considered by many to be an independent risk factor for poor neurodevelopment in premature infants. However, infants with BPD experience intermittent hypoxic episodes. This study was undertaken to determine whether intermittent hypoxic stress associated with BPD contributes to the development of neurological deficit. The model of BPD was produced in neonatal mice by exposure to hyperoxia (65% O2) for 4 weeks. Arterial blood gases, pulmonary mechanics, and histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 54 publications
(32 reference statements)
0
28
0
Order By: Relevance
“…We used hyperoxia to induce BPD-like changes in immature mice. After 4 weeks of hyperoxia (65% or 85% O 2 ), mice exhibit histologic and functional changes seen in human neonates with BPD: decreased alveolarization, respiratory acidosis, increased lung resistance, and decreased lung compliance (11,21). Because alveolarization in mice is completed by 2 to 3 weeks of postnatal age (12), we shortened hyperoxic exposure to 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used hyperoxia to induce BPD-like changes in immature mice. After 4 weeks of hyperoxia (65% or 85% O 2 ), mice exhibit histologic and functional changes seen in human neonates with BPD: decreased alveolarization, respiratory acidosis, increased lung resistance, and decreased lung compliance (11,21). Because alveolarization in mice is completed by 2 to 3 weeks of postnatal age (12), we shortened hyperoxic exposure to 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mice exposed to pyridaben for 2 weeks demonstrated a significantly (P 5 0.03) decreased body weight (6.12 6 0.99 g versus 7.39 6 0.52 g) and significantly greater mortality rate (chi square P 5 0.04) compared with their vehicle-treated controls. Similarly, hyperoxia-induced lung injury is associated with poor weight gain and significantly higher mortality rates (11,21). Thus, the same phenotype-an arrested alveolarization, pulmonary mitochondrial dysfunction, and retarded growth-has been induced by two distinctively different experimental challenges (exposure to hyperoxia or pyridaben).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ronchopulmonary dysplasia (BPD), a chronic lung disease that occurs in premature infants receiving prolonged ventilator support and oxygen supplementation, is associated with an increased risk of long-term neurodevelopmental impairments (1). Despite its limited predictive value, some clinical studies have also identified BPD as an independent risk factor for the development of neurofunctional deficits in premature infants, including cerebral palsy and developmental retardation, even in the absence of catastrophic brain injuries such as intraventricular hemorrhage and hypoxic-ischemic encephalopathy (1)(2)(3).…”
mentioning
confidence: 99%
“…Despite its limited predictive value, some clinical studies have also identified BPD as an independent risk factor for the development of neurofunctional deficits in premature infants, including cerebral palsy and developmental retardation, even in the absence of catastrophic brain injuries such as intraventricular hemorrhage and hypoxic-ischemic encephalopathy (1)(2)(3). No specific or effective treatment is currently available for the preterm infant brain.…”
mentioning
confidence: 99%